Low temperature combustion of cooking fume. - Muliyanni Zakaria. (2009)
As part of collaboration with National Enviroment Agency (NEA), this project aims to design and test a catalyst that allows low temperature combustion of cooking fume. Analysis of polycyclic aromatic hydrocarbons (PAHs) in fume samples by gas chromatography-mass spectrometry (GC-MS) and high performance liquid chromatography (HPLC) are also included. Sampling was done at different foodcourts by using a sampling pump attached to glass containing sorbents to trap the air of the foodcourt environment. Then, extraction of trapped cooking fume was done through sonication of flask filled with sorbents in an extracting solvent. Upon filtration and washing, the filtrate was then brought to a concentrate of 1.0 - 2.0 ml through a rotatory evaporator. These concentrated samples will be stored in the freezer prior to the GC-MS and HPLC analysis. Prior to testing, development of protocols was done. The results showed that HPLC is more appropriate for separating lower volatile PAHs of which carcinogenicity cannot be ignored. For catalysts synthesis, different methods were used from literature and were put under thermogravimetric analysis (TGA) test. TGA results showed that out of all the catalysts, FeZnOx demonstrated the best thermogravimetric property in terms of displaying the most weight loss. It was observed that FeZnOx reduce the cooking fume decomposition temperature by a significant amount compared to the other catalysts. It is concluded that a more objective protocol is needed to measure catalytic activity precisely.